Porcelain white dyed ABS (Acrylonitrile Butadiene Styrene) resin as well as product and preparation method thereof
By using raw materials such as ABS grafted latex, titanium dioxide emulsion and SAN resin, combined with emulsified wrapping treatment and melt blending methods, the problem of insufficient whiteness and performance of existing ABS resins was solved, and porcelain white dyed ABS resin with high whiteness, excellent mechanical properties and good fluidity was prepared, which is suitable for industrial production and reduces dust pollution.
Patent Information
- Application Number
- CN202311319120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-15
AI Technical Summary
While the existing porcelain white dye ABS resin improves the whiteness, the mechanical properties and fluidity are poor, which affects the application value of the material. At the same time, titanium dioxide dust has a negative impact on the environment and the human body.
ABS grafted latex, titanium dioxide emulsion, SAN resin, lubricant and antioxidant were used as raw materials, and porcelain white dye ABS resin with high whiteness, excellent mechanical properties and good fluidity was prepared by emulsification and wrapping treatment and melt blending.
It improves the whiteness of ABS resin, ensures the comprehensive performance of the material, including mechanical properties and fluidity, and avoids titanium dioxide dust pollution, making it suitable for industrial production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and particularly relates to a porcelain white dyed ABS resin, a product thereof and a preparation method thereof. Background Art
[0002] ABS resin is composed of three raw materials: butadiene, styrene and acrylonitrile. It has excellent properties such as good impact resistance, chemical resistance, easy processing and gloss. It is widely used in home appliances, automobiles, electronics and building materials. It is an important general-purpose plastic. With the increasingly fierce competition in the ABS resin market, porcelain white dyed customized ABS products have become a key development direction of the ABS market. At present, porcelain white dyed ABS resin is prepared by melt blending titanium dioxide and ABS resin. Due to the poor compatibility and dispersion of titanium dioxide and ABS resin, it is easy to agglomerate in the continuous phase, resulting in a decrease in the mechanical properties and flow properties of the material, affecting the application value of the material. At the same time, titanium dioxide dust will have a negative impact on both the environment and the human body.
[0003] Chinese patent CN113292811A provides a porcelain white super-hydrophobic ABS material and its preparation method. The invention mixes topological titanium dioxide and low surface energy modifier with ABS resin, and obtains a porcelain white super-hydrophobic ABS material by twin-screw extrusion, and its L value can reach 97.6, but the melt index of the composite material is reduced to 6.5g / 10min, and the material flowability is greatly reduced, which seriously affects the processability of the composite material.
[0004] Chinese patent CN113121740B provides a polybutadiene latex of high whiteness ABS resin and its preparation method and use. The prepared polybutadiene latex synthesized ABS resin has a whiteness of 89 and an impact strength of 395 J / m, but its preparation process is relatively complicated and costly, which is not conducive to industrial production, and the whiteness needs to be further improved. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a porcelain white dyed ABS resin having high whiteness, excellent mechanical properties and good fluidity, and a product and a preparation method thereof.
[0006] One aspect of the present invention provides a porcelain white dyed ABS resin, wherein the raw materials for preparing the resin include the following components in parts by weight: 22 to 28 parts of ABS grafted latex, 0.5 to 3 parts of titanium dioxide emulsion, 71 to 78 parts of SAN resin, 2 to 5 parts of lubricant, and 0.1 to 0.2 parts of antioxidant.
[0007] According to a specific embodiment of the present invention, the titanium dioxide emulsion includes the following components in parts by weight: 30 to 100 parts of titanium dioxide, 1 to 5 parts of emulsifier, 1 to 3 parts of electrolyte, and 200 to 500 parts of water.
[0008] According to a specific embodiment of the present invention, the emulsifier is selected from at least one of sulfonates, phosphates, enolates, sodium alkyl sulfosuccinates, and sodium branched alkyl alcohol ether phosphates. These emulsifiers are conducive to better emulsification of titanium dioxide and improve the dispersibility of titanium dioxide. The electrolyte is selected from any one of potassium carbonate, sodium carbonate and potassium hydroxide, and its function is to improve the stability of the titanium dioxide emulsion.
[0009] According to a specific embodiment of the present invention, the emulsifier is a mixture of sodium alkyl alcohol ether sulfosuccinate and sodium branched alkyl alcohol ether phosphate, in which the weight ratio of sodium alkyl alcohol ether sulfosuccinate to sodium branched alkyl alcohol ether phosphate is 0.5 to 3:1.
[0010] According to a specific embodiment of the present invention, the preparation method of titanium dioxide emulsion includes: mixing titanium dioxide, emulsifier, electrolyte and water, heating to 50-80° C., and keeping warm for 1-3 hours.
[0011] According to a specific embodiment of the present invention, the ABS grafted latex is obtained by grafting polybutadiene onto styrene monomer and acrylonitrile monomer. Based on the total weight of polybutadiene, styrene monomer and acrylonitrile monomer, the content of polybutadiene is 65-75%, the content of styrene monomer is 16-22%, and the content of acrylonitrile monomer is 3-19%; the particle size of the ABS grafted latex is 340-420 μm, and the solid content is 40%-50%.
[0012] According to a specific embodiment of the present invention, based on the total weight of all monomers forming the SAN resin, the content of acrylonitrile is 20-28%, and the content of styrene is 72-80%. Controlling each monomer within the above range can better improve production efficiency.
[0013] According to a specific embodiment of the present invention, the lubricant is selected from at least one of ethylene bisstearamide, polyethylene wax, and pentaerythritol stearate.
[0014] According to a specific embodiment of the present invention, the antioxidant is selected from any one of antioxidant 618, antioxidant 1076, and antioxidant 2246.
[0015] The second aspect of the present invention provides a method for preparing the aforementioned porcelain white dyed ABS resin, comprising: stirring and mixing ABS grafted latex and titanium dioxide emulsion and heating to 50-80°C, demulsifying and dehydrating to obtain powder, and then melt-blending the powder with SAN resin, lubricant and antioxidant and then extruding.
[0016] According to a specific embodiment of the present invention, the moisture content of the powder is 5-20%; and / or, a twin-screw extruder is used for melt extrusion; preferably, the temperature of each section of the twin-screw extruder is 180-240° C., and the screw speed is 240-260 rpm.
[0017] A third aspect of the present invention provides a plastic product, wherein the material of the plastic product comprises the aforementioned porcelain white dyed ABS resin.
[0018] The beneficial effects of the present invention are:
[0019] The raw materials for preparing the porcelain white dyed ABS resin of the present invention adopt ABS grafted latex, titanium dioxide emulsion, SAN resin, lubricant and antioxidant as raw materials and carry out suitable weight ratio, wherein the titanium dioxide in the titanium dioxide emulsion is subjected to emulsification and encapsulation treatment, and compared with the traditional addition of titanium dioxide dry powder, the titanium dioxide is emulsified to form nano-scale emulsion microspheres, which are added to the ABS grafted latex, stirred and mixed at the nano level, thereby reducing the agglomeration of titanium dioxide in the ABS grafted latex, achieving better dispersion effect, and preparing the porcelain white dyed ABS resin with high whiteness, excellent mechanical properties and good fluidity. The preparation method is simple and easy to operate, can form industrialized production, and the production process will not cause titanium dioxide dust pollution, which is conducive to improving the production and living environment. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the following examples, the particle size of the ABS grafted latex is 340-420 μm, and the solid content is 40%-50%.
[0022] Example 1
[0023] Weigh 95 parts of titanium dioxide, 3 parts of emulsifier sodium alkyl sulfosuccinate, 3 parts of potassium hydroxide, and 400 parts of water, add them into a kettle and stir evenly, heat the kettle to 60°C for emulsification reaction, and after the titanium dioxide is fully coated by the emulsifier, keep warm for 2 hours to obtain a titanium dioxide emulsion.
[0024] 0.5 parts of weighed titanium dioxide emulsion and 22 parts of ABS grafted latex were added to a container and mixed thoroughly. The container was heated to 60°C. 1 part of concentrated sulfuric acid was added to the mixed latex, and demulsified at 80°C, and then dehydrated to obtain a powder with a water content of 5%. The obtained powder was mixed with 78 parts of SAN resin, 3 parts of ethylene bis stearamide, and 0.2 parts of antioxidant 168, and melt blended and extruded in a twin-screw extruder. The temperatures of each zone of the extruder were 180°C, 200°C, 200°C, and 220°C, respectively, and the screw speed was 240-260rpm. The extruded material strips were cooled by water and pelletized by a pelletizer to obtain porcelain white dyed ABS resin. The samples were injection molded into parts by an injection molding machine and performance tested.
[0025] Example 2
[0026] Weigh 60 parts of titanium dioxide, 2.4 parts of emulsifier sodium alkyl sulfosuccinate, 2 parts of potassium hydroxide, and 240 parts of water, add them into a kettle and stir evenly, heat the kettle to 80°C for emulsification reaction, and after the titanium dioxide is fully coated by the emulsifier, keep warm for 2 hours to obtain a titanium dioxide emulsion.
[0027] 1 part of weighed titanium dioxide emulsion and 24 parts of ABS grafted latex are added to a container and mixed and stirred thoroughly. The container is heated to 60°C. 1 part of concentrated sulfuric acid is added to the mixed latex, and demulsification is performed at 90°C. Then, dehydration treatment is performed to obtain a powder, and the water content of the powder is 10%; the obtained powder is mixed with 75 parts of SAN resin, 5 parts of pentaerythritol stearate, and 0.2 parts of antioxidant 168, and melt blending and extrusion are performed in a twin-screw extruder. The temperatures of each zone of the extruder are 180°C, 200°C, 200°C, and 220°C, respectively, and the screw speed is 240-260rpm. The extruded material strips are cooled by water and pelletized by a pelletizer to obtain porcelain white dyed ABS resin. The samples are injection molded into parts by an injection molding machine and performance tests are performed.
[0028] Example 3
[0029] Weigh 100 parts of titanium dioxide, 5 parts of a mixture of emulsifier sodium alkyl ether sulfosuccinate and sodium branched alkyl alcohol ether phosphate, 2 parts of potassium hydroxide, and 500 parts of water, wherein the weight ratio of the emulsifier sodium alkyl ether sulfosuccinate to sodium branched alkyl alcohol ether phosphate is 1:1, add them into an autoclave and stir evenly, heat the autoclave to 50°C for emulsification reaction, and after the titanium dioxide is fully coated by the emulsifier, keep warm for 3 hours to obtain a titanium dioxide emulsion.
[0030] 1 part of weighed titanium dioxide emulsion and 28 parts of ABS grafted latex are added to a container and mixed and stirred thoroughly. The container is heated to 60°C, 1 part of concentrated sulfuric acid is added to the mixed latex, and the emulsion is broken at 80°C, and then dehydrated to obtain a powder, the water content of the powder is 10%; the obtained powder is mixed with 71 parts of SAN resin, 3 parts of a mixture of pentaerythritol stearate and ethylene bis stearamide, and 0.1 parts of antioxidant 168, wherein the weight ratio of pentaerythritol stearate to ethylene bis stearamide is 2:1, and melt blending and extrusion are carried out in a twin-screw extruder. The temperatures of each zone of the extruder are 180°C, 200°C, 200°C, and 220°C, respectively, and the screw speed is 240-260rpm. The extruded material strips are cooled by water and pelletized by a pelletizer to obtain a porcelain white dyed ABS resin. The samples are injection molded into parts by an injection molding machine and the performance is tested.
[0031] Example 4
[0032] Weigh 30 parts of titanium dioxide, 1 part of emulsifier sodium branched alkyl alcohol ether phosphate, 1 part of potassium hydroxide, and 200 parts of water, add them into a kettle and stir evenly, heat the kettle to 60°C for emulsification reaction, and after the titanium dioxide is fully coated by the emulsifier, keep warm for 1 hour to obtain a titanium dioxide emulsion.
[0033] 3 parts of weighed titanium dioxide emulsion and 24 parts of ABS grafted latex are added to a container and mixed and stirred thoroughly. The container is heated to 60°C. 1 part of concentrated sulfuric acid is added to the mixed latex, and the emulsion is broken at 80°C, and then dehydrated to obtain a powder with a water content of 20%; the obtained powder is mixed with 73 parts of SAN resin, 2 parts of pentaerythritol stearate, and 0.2 parts of antioxidant 2246, and melt blended and extruded in a twin-screw extruder. The temperatures of each zone of the extruder are 180°C, 200°C, 200°C, and 220°C, respectively, and the screw speed is 240-260rpm. The extruded material strips are cooled by water and pelletized by a pelletizer to obtain porcelain white dyed ABS resin. The samples are injection molded into parts by an injection molding machine and the performance is tested.
[0034] Comparative Example 1
[0035] According to weight, 24 parts of ABS grafted powder, 76 parts of SAN resin, 3 parts of pentaerythritol stearate, and 0.2 parts of antioxidant 168 were weighed and mixed, and melt blended and extruded in a twin-screw extruder. The temperature of each zone of the extruder was 180°C, 200°C, 200°C, and 220°C, and the screw speed was 240-260rpm. The extruded material strips were water-cooled and pelletized by a pelletizer to obtain porcelain white dyed ABS resin. The samples were injection molded into parts by an injection molding machine and performance tested.
[0036] Comparative Example 2
[0037] According to weight, 24 parts of ABS grafted powder, 1 part of titanium dioxide, 75 parts of SAN resin, 3 parts of pentaerythritol stearate, and 0.2 parts of antioxidant 168 were weighed and mixed, and melt blended and extruded in a twin-screw extruder. The temperature of each zone of the extruder was 180°C, 200°C, 200°C, and 220°C, and the screw speed was 240-260rpm. The extruded material strips were water-cooled and pelletized by a pelletizer to obtain porcelain white dyed ABS resin. The samples were injection molded into parts by an injection molding machine and performance tested.
[0038] Comparative Example 3
[0039] According to weight, 28 parts of ABS grafted latex, 1 part of titanium dioxide, 71 parts of SAN resin, 3 parts of pentaerythritol stearate, and 0.1 parts of antioxidant 168 were weighed and mixed, and melt blended and extruded in a twin-screw extruder. The temperature of each zone of the extruder was 180°C, 200°C, 200°C, and 220°C, and the screw speed was 240-260rpm. The extruded material strips were water-cooled and pelletized by a pelletizer to obtain porcelain white dyed ABS resin. The samples were injection molded into parts by an injection molding machine and performance tested.
[0040] The test performances of Examples 1 to 4 and Comparative Examples 1 to 3 are shown in the table below.
[0041]
[0042] From the performance test results of Examples 1 to 4 and Comparative Examples 1 to 3, it can be concluded that the ABS resin in Comparative Example 1 has no colorant added, and its whiteness is 62.2. In Examples 1 to 4, the titanium dioxide that has been emulsified is mixed with the ABS graft polymer and dehydrated to blend with the SAN resin, and its whiteness can reach up to 94.2, which is greatly improved. The mechanical properties and fluidity of the ABS resin prepared in Examples 1 to 4 are not much different from those in Comparative Example 1. The titanium dioxide in Comparative Examples 2 to 3 has not been emulsified, and its impact performance is as low as 10.8 kJ / m 2 , which is about 50% lower than that of comparative example 1, and other properties are all reduced, which seriously affects the application value of the material.
[0043] In summary, the porcelain white dyed ABS resin proposed in the present invention improves whiteness while ensuring the comprehensive performance of the material, and has extremely high application value and development prospects.
[0044] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A porcelain white dyed ABS resin, characterized in that: The raw materials for its preparation include the following components by weight: ABS grafted latex 22-28 parts, titanium dioxide emulsion 0.5-3 parts, SAN resin 71-78 parts, lubricant 2-5 parts, antioxidant 0.1-0.2 parts.
2. The porcelain white dyed ABS resin according to claim 1, characterized in that: The titanium dioxide emulsion comprises the following components by weight: 30 to 100 parts of titanium dioxide, 1 to 5 parts of emulsifier, 1 to 3 parts of electrolyte, and 200 to 500 parts of water.
3. The porcelain white dyed ABS resin according to claim 2, characterized in that: The emulsifier is selected from at least one of sulfonates, phosphates, enolates, sodium alkyl sulfosuccinates, and sodium branched alkyl alcohol ether phosphates; and / or the electrolyte is selected from any one of potassium carbonate, sodium carbonate, and potassium hydroxide.
4. The porcelain white dyed ABS resin according to claim 3, characterized in that: The emulsifier is a mixture of sodium alkyl alcohol ether sulfosuccinate and sodium branched alkyl alcohol ether phosphate. In the mixture, the weight ratio of sodium alkyl alcohol ether sulfosuccinate to sodium branched alkyl alcohol ether phosphate is 0.5-3:
1.
5. The porcelain white dyed ABS resin according to any one of claims 2 to 4, characterized in that: The preparation method of the titanium dioxide emulsion comprises: mixing titanium dioxide, an emulsifier, an electrolyte and water, heating to 50 to 80° C., and keeping the temperature for 1 to 3 hours.
6. The porcelain white dyed ABS resin according to claim 1, characterized in that: The ABS grafted latex is obtained by grafting polybutadiene with styrene monomer and acrylonitrile monomer. Based on the total weight of polybutadiene, styrene monomer and acrylonitrile monomer, the content of polybutadiene is 65-75%, the content of styrene monomer is 16-22%, and the content of acrylonitrile monomer is 3-19%. The particle size of the ABS grafted latex is 340-420 μm, and the solid content is 40%-50%.
7. The porcelain white dyed ABS resin according to claim 1, characterized in that: Based on the total weight of all monomers forming the SAN resin, the content of acrylonitrile is 20-28%, and the content of styrene is 72-80%.
8. The porcelain white dyed ABS resin according to claim 1, characterized in that: The lubricant is selected from at least one of ethylene bisstearamide, polyethylene wax, and pentaerythritol stearate.
9. The porcelain white dyed ABS resin according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 618, antioxidant 1076, and antioxidant 2246.
10. A method for preparing the porcelain white dyed ABS resin according to any one of claims 1 to 9, characterized in that: The preparation method comprises: The ABS grafted latex and titanium dioxide emulsion are stirred and mixed and heated to 50-80°C, demulsified and dehydrated to obtain powder, and then the powder is melt-blended with SAN resin, lubricant and antioxidant and then extruded.
11. The preparation method according to claim 10, characterized in that: The moisture content of the powder is 5-20%; and / or, the powder is melt extruded by a twin-screw extruder; Preferably, the temperature of each section of the twin-screw extruder is 180-240° C., and the screw speed is 240-260 rpm.
12. A plastic product, characterized in that: The material of the plastic product comprises the porcelain white dyed ABS resin as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
A polybutadiene latex for preparing high-whiteness ABS resin, its preparation method and uses
CN113121740B
Porcelain white super-hydrophobic ABS material and preparation method thereof
CN113292811A
High-impact while household electrical appliance ABS composite material and preparation method therefor
CN104910539A
High-fluidity and high-anti-impact ABS resin and preparation method thereof
CN105733120A
Preparation method of lead-free ray radiation preventing rubber composite
CN108586777A